The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1212/nxi.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Fumarate Treatment in Patients With Primary Progressive Multiple Sclerosis

Abstract: Background and ObjectiveTo study whether dimethyl fumarate is superior to placebo in decreasing CSF concentrations of neurofilament light chain (NFL) in patients with primary progressive MS (PPMS).MethodsIn the double-blind, placebo-controlled phase 2 study dimethyl FUMArate treatment in Progressive Multiple Sclerosis (FUMAPMS), patients with PPMS were randomly assigned to treatment with 240 mg dimethyl fumarate or placebo in a 1:1 ratio for 48 weeks. The primary endpoint was change in concentration of NFL in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“… 9 Recently, we performed a randomized, placebo-controlled trial investigating dimethyl fumarate (DMF) treatment in patients with PPMS. 10 Like many of the previous studies of disease-modifying therapies in patients with PPMS, we found no effect of DMF after 48 weeks of treatment. 10 Concurrent with the clinical trial, we investigated the immunologic effects of DMF treatment.…”
supporting
confidence: 80%
See 2 more Smart Citations
“… 9 Recently, we performed a randomized, placebo-controlled trial investigating dimethyl fumarate (DMF) treatment in patients with PPMS. 10 Like many of the previous studies of disease-modifying therapies in patients with PPMS, we found no effect of DMF after 48 weeks of treatment. 10 Concurrent with the clinical trial, we investigated the immunologic effects of DMF treatment.…”
supporting
confidence: 80%
“… 10 Like many of the previous studies of disease-modifying therapies in patients with PPMS, we found no effect of DMF after 48 weeks of treatment. 10 Concurrent with the clinical trial, we investigated the immunologic effects of DMF treatment. This showed substantial effects of DMF on circulating B cells and T cells and a reduced number of CD4 + T cells CSF in PPMS but no clear effects on other biomarkers of intrathecal inflammation.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Serum Simoa NfL levels remained high in nonresponders with clinical relapse, whereas NfL decreased significantly during follow-up (24 months) in patients with a relapse-free course [27] DMF (RRMS, 52; HC, 23; placebo, 52) CSF Simoa RRMS patients had higher NfL levels at baseline compared to HC (mean, 2,368 pg/mL vs. 417 pg/mL; p < 0.001), and 72% of samples showed a reduction to levels comparable to HCs after 1 year of treatment [25] DMF (DMF, 27; placebo, 27) CSF ELISA Mean change in CSF NfL level did not differ between groups (mean difference, 99 ng/L; 95% CI, -292 to 491; p = 0.61) [28] Fingolimod (RRMS, 36) CSF ELISA Fingolimod proved effective in decreasing NfL levels in RRMS (-326 pg/mL, 83.3% with reduction, p = 0.002), and the NfL levels one year after treatment were higher in patients with relapse during the study vs. those without (mean, 1,448 pg/mL vs. 384 pg/mL; p = 0.014) [29] Natalizumab (RRMS, 96) Serum Simoa…”
Section: Glatiramer Acetate (Rrms 20) and Inf-β (Rrms 12)mentioning
confidence: 94%
“… 15 Since OCR did and dimethyl fumarate did not show significant effects in clinical trials for people with primary progressive multiple sclerosis, divergent effects on the intrathecal lymphocyte composition could reveal important mechanisms in the modulation of primary progressive multiple sclerosis. 5 , 28 Studying lymphocyte fractions in the CSF is especially relevant, since the pathology of primary progressive multiple sclerosis has been argued to be more dependent on compartmentalized inflammatory and degenerative processes and not on CNS recruitment of circulating lymphocytes. 29 Additionally, phenotypically distinct populations have been reported to patrol the intrathecal compartment in people with advanced progressive multiple sclerosis, and monoclonal antibodies as OCR do not cross the blood–brain barrier.…”
Section: Introductionmentioning
confidence: 99%